(untitled) (Journal of Comparative & International Higher Education, 2024)
The paper argues that the conflict in Ukraine is promoting and accelerating the Westernization of the region’s higher education. The paper employs Mignolo’s (2011) geopolitics of knowledge as the theoretical framework to illustrate how internationalization promotes the adoption of Western/English liberal education and the war is speeding up the process. Using focus groups and open-ended questionnaires, I capture conversations with local and international graduate students in Kazakhstan to demonstrate that Western education is acquired to 1) accelerate the de-Russification of Kazakhstan by moving away from the former colonizer, 2) use English to undermine the Russian language and cement Kazakhstan’s independence from Russia, 3) acquire internationally recognized English credentials for global/Western competitiveness. The participants in this study framed their decision to pursue university graduate studies as freedom from the Soviet system, de-Russification, acquiring cultural capital and global competence, underscoring the high value that some graduate students have for an English credential.